Analytical model of Kuwait power consumption - Muhaisen, Naser; Ahmed, Musse Mohamud; Khan, Sheroz; Habaebi, Mohamed Hadi; Ahmed, Nabil; Arshad, Atika (IEEE, 2017)
In this paper, assessing an analytical model of Kuwait City power consumption is focused. This includes data per person of energy demand, increasing trends over the years to investigate the rapidly increasing power demand due to the growing number of the population in Kuwait and due to modernization of life style. Therefore, this paper focuses on the analytical model for Kuwait city power consumption showing how the peak-hours demand can be complemented by the solar potential from rooftop solar panels. If the solar energy is associated with the highly potential wind power contribution in DG form, this will help in the existing capacity deficiency at the national grid level be met by alternative source of energy. The results of this work will help considerably in reducing the investments in the ongoing practice of building new power plants. The renewable energy sources in the form of Distributed Generation (DG), both renewable and non-renewable, have become an attractive solution for meeting the energy demand in areas having no access to electricity supply from utility grid.